2017
DOI: 10.1073/pnas.1621513114
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for specific ligation of the peroxisome proliferator-activated receptor δ

Abstract: The peroxisome proliferator-activated receptor (PPAR) family comprises three subtypes: PPARα, PPARγ, and PPARδ. PPARδ transcriptionally modulates lipid metabolism and the control of energy homeostasis; therefore, PPARδ agonists are promising agents for treating a variety of metabolic disorders. In the present study, we develop a panel of rationally designed PPARδ agonists. The modular motif affords efficient syntheses using building blocks optimized for interactions with subtype-specific residues in the PPARδ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 54 publications
0
54
0
Order By: Relevance
“…Fenofibrate is an antilipemic agent that is an agonist for PPARα which results in increased fatty acid oxidation, triglyceride elimination, an upregulation of lipoprotein lipase activity and very low-density lipoprotein (VLDL) catabolism. Also, mice with absent PPARα became obese with age as compared to the mice that had PPARα [ 27 - 28 ]. Medium-chain fatty acids (saturated and unsaturated) are the ligands for PPARα which stimulates the increased expression of genes encoding enzymes for β-oxidation of fatty acids in mitochondria.…”
Section: Reviewmentioning
confidence: 99%
“…Fenofibrate is an antilipemic agent that is an agonist for PPARα which results in increased fatty acid oxidation, triglyceride elimination, an upregulation of lipoprotein lipase activity and very low-density lipoprotein (VLDL) catabolism. Also, mice with absent PPARα became obese with age as compared to the mice that had PPARα [ 27 - 28 ]. Medium-chain fatty acids (saturated and unsaturated) are the ligands for PPARα which stimulates the increased expression of genes encoding enzymes for β-oxidation of fatty acids in mitochondria.…”
Section: Reviewmentioning
confidence: 99%
“…Wu et al (5) rationally designed ligands to occupy both of these arms of PPARδ, focusing on interacting with residues not shared with the α-and γ-types in a successful attempt to improve the specificity of their compounds. Similar to the GW501516 compound, their ligands all have a carboxyl head group, which interacts with the AF-2 region, but their ligands are an order-of-magnitude more selective for PPARδ than previous compounds.…”
Section: Conservation Of Specific Residues In the Lbdmentioning
confidence: 99%
“…The loop is so flexible as to be almost disordered in some structures, and is difficult enough to model that it is missing from many available crystal structures of PPAR nuclear receptor LBDs. Through comparing structures of PPARδ bound to conformationally distinct ligands, Wu et al (5) have found a tryptophan residue in this loop region that dramatically changes conformation upon binding of different ligands. The authors posit that the resulting change in conformation because of the bulkiness of the ligand tail is a mechanism of ligand selectivity by which PPAR nuclear receptors may bind to distinct ligands.…”
Section: A Unique Trp Residue In a Flexible Loop Of Pparδ Aids In Submentioning
confidence: 99%
“…Although PPAR-δ has a narrower LBD relative to PPARs-α and-γ, binding pocket characteristics allow potential interaction with a variety of ligands, albeit many appear to bind at relatively low affinities [ 13 ]. While many potential endogenous ligands have been suggested in the literature, there is still some uncertainty about the physiological significance [ 14 ]. Selective ligands targeting PPAR-δ have also been developed, although none have been approved for clinical use to date [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…While many potential endogenous ligands have been suggested in the literature, there is still some uncertainty about the physiological significance [ 14 ]. Selective ligands targeting PPAR-δ have also been developed, although none have been approved for clinical use to date [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%